Tetrabromobisphenol A (TBBPA) degradation in anaerobic biosystems: from bioengineering to meta-omics - Macêdo, Williane Vieira (2022)
The presence of organic micropollutants (OMPs) in aquatic ecosystems is usually associated with the disposal of industrial and municipal effluents from wastewater treatment plants in water bodies. Tetrabromobisphenol A (TBBPA) is a brominated flame retardant applied to plastics, coatings, building materials, and electronics, and poses a serious threat to the human health and to aquatic ecosystems due to its endocrine disruptor, immunotoxic, and neurotoxic effects. The optimization of anaerobic biosystems for the degradation of micropollutants and the microbiome involved in the process remains little explored. In this doctoral thesis, a series of experiments have been conducted to extend the knowledge on some of the gaps related to the biodegradation of TBBPA. Firstly, an accurate and sensitive liquidliquid microextraction technique followed by high performance liquid chromatography separation coupled with electrospray ionization tandem mass spectrometry detection (HPLC-ESI-MS/MS) method to determine the presence of TBBPA in complex environmental matrices is proposed. In sequence, by combining a series of degradation and multiomics experiments, we were able to identify the microorganisms actively degrading tetrabromobisphenol A (TBBPA) at environmentally relevant concentrations in anaerobic settings and their putative functional expression in long-term exposure to the pollutant. The results from a total of four anaerobic continuous bioreactors suggested the specific stage of the anaerobic digestion in which the degradation of TBBPA takes place, the relevance of the adsorption of the pollutant onto the biomass, the degradation kinetics, and the microbiome profile throughout the operational period by amplicon sequencing of the 16SrRNA gene. Additionally, the biomass from the best-performance bioreactor was applied in labelled metaproteomics (protein stable isotope probing, protein-SIP) and metagenomics experiments. By linking metagenomic, predicted functional, and metaproteomic data, the microorganisms involved in the degradation of the micropollutant were identified. From metagenome-assembled genomes (MAGs) containing coding sequences for the labelled peptides, predicted proteomes were generated and the putative metabolic pathways were described. Proteins involved in the hydrolytic cleavage of carbon-halogen bonds, benzoate degradation, transport of aromatic compounds, and resistance to xenobiotics were identified. These findings are in agreement with the initial predictions based on the correlation of the bioreactor\'s performance and the temporal characterization of the microbiome, the metabolic routes undergoing acidogenic biosystems, and the detection of total phenols as one of the possible degradation products.